Risk-Adapted Treatment in Clinical Stage I Testicular Seminoma: The Third Spanish Germ Cell Cancer Group Study - Aparicio, Jorge; Maroto, Pablo; García del Muro, Xavier; Guma, Josep; Sánchez-Muñoz, Alfonso; Margelí, Mireia; Domenech, Montserrat; Bastús, Romá; Fernández, Antonio; Lopez-Brea, Marta; Terrassa, Josefa; Meana, Andrés; et al. (Editorial Roster. ASCO publications, 2011)
Purpose To confirm the efficacy of a risk-adapted treatment approach for patients with clinical stage I seminoma. The aim was to reduce both the risk of relapse and the proportion of patients receiving adjuvant chemotherapy while maintaining a high cure rate. Patients and Methods From 2004 to 2008, 227 patients were included after orchiectomy in a multicenter study. Eighty-four patients (37%) presented no local risk factors, 44 patients (19%) had tumors larger than 4 cm, 25 patients (11%) had rete testis involvement, and 74 patients (33%) had both criteria. Only the latter group received two courses of adjuvant carboplatin, whereas the rest were managed by surveillance. Results After a median follow-up time of 34 months, 16 relapses (7%) have been documented (15 [9.8%] among patients on surveillance and one [1.4%] among those treated with carboplatin). All relapses occurred in retroperitoneal lymph nodes, except for one case in pelvic nodes. Median node size was 25 mm, and median time to recurrence was 14 months. All patients were rendered disease-free with chemotherapy. The actuarial 3-year disease-free survival rate was 88.1% (95% CI, 82.3% to 93.9%) for patients on surveillance and 98.0% (95% CI, 94.0% to 100%) for those treated with adjuvant chemotherapy. Overall 3-year survival was 100%. Conclusion With the limitations of the short follow-up duration, we confirm that a risk-adapted approach is effective for stage I seminoma. Adjuvant carboplatin seems adequate treatment for patients with 2 risk criteria, as is active surveillance for those with 0 to one risk factors. More reliable predictive factors are needed to improve the applicability of this model.
Este artículo ha sido publicado en Journal of Clinical Oncology El archivo que deposito es el posprint que me ha enviado la editorial, lo cual aclaro para para que quede constancia y no haya confusión al respecto Esta versión tiene Licencia Creative Commons CC-BY-NC-ND
Keywords: Testículos - Cáncer - Tratamiento; Testicular Seminoma; Stage I; Risk-Adapted Treatment